Incidencia de insectos plagas y controladores biológicos en plantaciones de sorgo (sorghum bicolor) en Buenos Aires Provincia Picota - Meléndez Amasifuén, Carlos Fernando (2000)
The present research work was carried out with the objective of determining the existence of insect pest and beneficial present in all sorghum crop phenological stage. The experiment was carried out from the month of October 1999 to January 2000 in the estate of the company San Fernando, located in the District of Buenos Aires, province of cherry, Department of San Martin. The soil was clayey texture with a pH of 7.8 and organic content of 3%. The ground is located at an altitude of 223 metres above sea level. With average rainfall of 1 200 mm/year. the evaluations took place in a net area of 600m 2 making a total of 6 parcels, with 5 sub plots in each of them. For the statistical analysis used T test both for insect pests as beneficial, with 0.05% probability where it was highly significant presence of insects plague upon the beneficial. The largest population of harmful insects corresponded to the orders Lepidoptera and Homoptera. Beneficial insects are of the order Coleoptera, Hymenoptera, Dermaptera, Hemiptera, Arachneida and Neuroptera During the execution of the experimental work, weather conditions was one of the adverse factors to driving culture especially the temperature registering the largest increase at the time of flowering, stage in which the crop needs more precipitation.